HEALTHCARE PROFESSIONALS’ VIEWS ON HEALTH TECHNOLOGY ADOPTION IN URBAN HOSPITALS OF ALMATY - Tolegenova S.; Maukenova A.; Abinova A. (Modern Scientific Technology, 2025)
Innovation is crucial for improving healthcare outcomes but faces barriers like high costs and regulatory constraints. Research is needed to better understand how factors like leadership and organizational climate drive innovation readiness throughout the process. The aim is to compare physicians’ and nurses’ attitudes toward health technologies, innovation, and evidence-based practice in Almaty hospitals, highlighting barriers, training needs, and opportunities for improved implementation and collaboration. This study used a questionnaire to assess healthcare professionals’ perceptions of innovation, teamwork, and health technology assessment (HTA) processes. The questionnaire was validated by experts and included sections on HTA perceptions and demographics. Piloted with 10 staff members, it was offered in Kazakh and Russian. Data were collected anonymously via an online form in the first trimester of 2025, with 361 responses (136 doctors, 225 nurses). Statistical analysis was done using SPSS and Excel, with chi-square tests to compare groups. Doctors were younger than nurses (p = 0.014), with more in the 20-30 age group. Physicians reported greater use of medical databases (p = 0.004) and had higher confidence in the benefits of new technologies, including improving care quality, efficiency, and reputation (p < 0.001). Nurses were more aware of the Joint Commission and the process of introducing new technologies (p < 0.001), and more reported improvements in care quality due to new technologies (p = 0.043). Nurses also felt technologies simplified documentation (p < 0.001) and improved efficiency (p = 0.001), but faced integration challenges and limited training. Physicians showed greater use of academic resources and confidence in advanced technologies, while nurses emphasized collaboration with statistical departments and integrating mid-level staff. Both groups faced similar challenges, such as training and equipment shortages, with physicians experiencing more difficulties. Policymakers should focus on improving access to training, enhancing cross-disciplinary collaboration, and addressing resource barriers to better implement health technologies